Optimal Control as a Graphical Model Inference Problem - Kappen, Hilbert; Gomez, Vicenç; Opper, Manfred (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
In this paper we show the identification between stochastic optimal control computation and probabilistic inference on a graphical model for certain class of control problems. We refer to these problems as Kullback-Leibler (KL) control problems. We illustrate how KL control can be used to model a multi-agent cooperative game for which optimal control can be approximated using belief propagation when exact inference is unfeasible.